DECOLONIZING ENVIRONMENTAL COMMUNICATION THROUGH ISLAMIC ETHICS: MEDIA FRAMING OF GREEN ECONOMY AND GREENWASHING IN INDONESIA - Mahsun, Moch; Bakhri, Saiful; Satriyo, Cindy Charisma; Yazid, Azy Athoillah (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2026)
This research focuses on implementing digital media for Islam’s green economy and greenwashing. The research focuses on the decolonization of environmental communications. Using content from the three of the most prominent platforms Kompas.com, Detik.com, and TimesIndonesia.co.id and using the interpretive paradigm, purposive sampling of 45 articles from 2022-2024 on each platform disentangles the empirical evidence in the sustainability and greenwashing discourse in acting and using Islamic ethical concepts in the persuasive framework and communication of khalifah, mīzān, maqāṣid al-sharīʿah, and sadd al-dharīʿah. The ethical, albeit fractured, mediation of legitimizing the articulation of green and sustainable ethics is the function of the platforms. Kompas.com is Critical–Reformist in its jurisprudential orientation and Detik.com from within a social construct of ethical individualized responsibility, while Times from the Islamic green ethics realm is primarily rhetorical. These collectively address the instrumental Islamic ethics of modernization of development discourse. Islamic legal maxims, while being highly instrumental and greenwashing within its construct, tend to be selective, cautious, and restrictive. This study enriches the theorization of media and religion within the decolonial discourse paradigms of communication and rhetoric-ecology.